Insights into The Diversity of NepenthesL. (Nepenthaceae) Across Peninsular Malaysia, Including The First Sighting of an Undescribed Taxon with Flared Peristomes and Quadruple-Row Ventral Wings - Amin-Asyraf Tamizi; Salasiah Mohamad; Mohamad-Alias Shakri; Nurshahidah Mohd-Rusli; Noriha Mat-Amin; Muhamad-Arif Mohamad-Jamali (Penerbit UTHM, 2024)
Non-Indexed Publication